High and low level constructions in dictionaries and constructiCons: the interplay between lexical and syntactic information in CASA|Con - Herbst, Thomas (Lexicographica, 2024)
After outlining the concept of a constructiCon and discussing the relationship of lexicography and constructicography, the focus of this article lies on the CASA ConstruCtiCon project for the English language. The treatment of different types of constructions in CASA|Con is discussed such as argument structure constructions, sentence type constructions, and tense and aspect constructions. In contrast to such constructions at a high level of abstraction a few examples involving a low level of abstraction are being discussed and it is argued that such seemingly unidiomatic constructions constitute an important element of idiomatic language use. Finally, it is shown that the vast majority of constructions are related to lexical material and that thus bringing together what used to be separated into lexical and grammatical phenomena makes a lot of sense not only in terms of linguistic theory but also with respect to works of reference.
CRIS-Team Scopus Importer:2024-12-06
Keywords: argument structure constructions; collocation; constructicography; constructiCon; construction; contrastive analysis; idiomaticity; lexicography; phraseology; usage-based approach